Human rights and the Internet - Liddicoat, Joy (Cambridge, United Kingdom; Chicago, IL . Intersentia Ltd, 2021)
The past decade has witnessed unprecedented use of the Internet for both advancing and suppressing human rights, giving rise to complex new issues that can both inspire and overwhelm. With ever-growing concerns about the (non-)regulation of our digital environment, it is surprising that both the theoretical and practical application of human rights to the Internet and our online lives remain unclear. This book is a short and accessible introduction to the concepts of human rights, the Internet and the emergence of an era of human rights online as a new legal challenge. It will be of interest to a broad range of readers: policy makers and informed citizens, lawyers working with human rights defenders, and legal and human rights academics examining the emergence of this legal field.
Includes bibliographical references and index.
Keywords: Internet -- Law and legislation; Internet -- Political aspects; Human rights; Digital media -- Law and legislation; Internet -- Political aspects; Internet -- Law and legislation; Human rights; Digital media -- Law and legislation